SMART CAR PARKING USING WI-FI AND BLYNK APP - Mr. Hulmani Appasha; Mr. Korachgaon Abhishek; Mr. Khilari V.S. (International Engineering Journal For Research & Development, 2020)
This paper describes a design of effective information system that can monitor the vehicle condition in traveling, detect the accident of the vehicle and accidents due to excessive alcohol consumption, collision of two vehicles due to negligence or a sleepy driver and theft detection system. A prototype of smart parking that allows drivers to effectively find the vacant parking spaces is also been designed and implemented in this paper. By periodically learning the parking status from the sensor networks deployed in parking lots, the drivers are allowed to access this information with their personal communication devices and exactly know which parking slots are vacant. This particular application uses internet of things for accessing the information with their mobile phones. This system has the potential to simplify the operations of parking systems, as well as alleviate traffic congestion caused by parking searching and would definitely make people follow the traffic rules and ensure safety. The developed system is reliable, low cost and user friendly.